First data on the biological variation and quality specifications for plasma ammonia concentrations in healthy subjects - Ucar, Fatma; Erden, Gonul; Ozdemir, Seyda; Ozcan, Nurgul; Bulut, Erdem; Ozturk, Alpaslan (Clinical chemistry and laboratory medicine, 2016)
Most of the factors causing preanalytical and analytical variation in ammonia measurement have been identified. Biological variation data for ammonia is still lacking. We therefore estimated the components of biological variation (within-subject=CVI and between-subject=CVG), reference change value (RCV) and quality specifications for ammonia in a group of healthy individuals using fresh and frozen plasma samples. Blood samples from 20 healthy subjects were collected in K2EDTA tubes daily over a period of 4 consecutive days from each subject. Each plasma sample was split into two aliquots; one was immediately analyzed as the samples were collected and the other was stored -80 °C until testing at the end of the collection period and analyzed at once in one analytical run. All samples were analyzed in duplicate. Estimations were calculated according to Fraser and Harris methods. CVI value for fresh samples (13.78%) was significantly lower than that in frozen samples (18.91%) (p<0.001). However, there was no statistically significant difference in CVG values between fresh (16.91%) and frozen (18.43%) samples (p=0.570). The index of individuality did not exceed 1.4 for fresh and frozen samples. The estimated RCVs were high for both fresh and frozen samples (43.37% and 56.85%, respectively). Quality specifications were established. The present study for the first time described the components of biological variation for ammonia in healthy individuals. These data regarding biological variation of ammonia could be useful for a better evaluation of ammonia test results in clinical interpretation and for determining quality specifications based on biological variation.